2011
DOI: 10.1523/jneurosci.3638-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dystrobrevin Controls Neurotransmitter Release and Muscle Ca2+Transients by Localizing BK Channels inCaenorhabditis elegans

Abstract: Dystrobrevin is a major component of a dystrophin-associated protein complex (DAPC). It is widely expressed in mammalian tissues including the nervous system, where it is localized to the presynaptic nerve terminal with unknown function. In a genetic screen for suppressors of a lethargic phenotype caused by a gain-of-function (gf) isoform of SLO-1 in C. elegans, we isolated multiple loss-of-function (lf) mutants of the dystrobrevin gene dyb-1. dyb-1(lf) phenocopied slo-1(lf), causing increased neurotransmitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Partially explaining the opposite effects, EETs activate whereas 20-HETE inhibits large conductance Ca 2+ -activated potassium (BK) channels in vascular smooth muscle cells ( 50,53 ). In C. elegans , BK channels are involved in regulating muscle Ca 2+ -transients ( 54,55 ) as well as neurotransmitter release at neuromuscular junction ( 56 ). 17,18-EEQ shares and, in several vascular beds, even largely exceeds the vasodilatory ( 57 ) and BK channel activating effects of EETs ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Partially explaining the opposite effects, EETs activate whereas 20-HETE inhibits large conductance Ca 2+ -activated potassium (BK) channels in vascular smooth muscle cells ( 50,53 ). In C. elegans , BK channels are involved in regulating muscle Ca 2+ -transients ( 54,55 ) as well as neurotransmitter release at neuromuscular junction ( 56 ). 17,18-EEQ shares and, in several vascular beds, even largely exceeds the vasodilatory ( 57 ) and BK channel activating effects of EETs ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…gating | structure-function | ion channel pore L arge-conductance, Ca 2+ -activated K + (BK) channels regulate physiological processes such as neurotransmitter release, smooth muscle contraction, and hair cell frequency tuning (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). BK channel proteins are homotetramers formed by BK α-subunits, which then associate with different β-or γ-subunits in a tissue-specific manner (13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…[29]. It has been suggested that, in skeletal muscle from C. elegans, BK Ca channel expresses and functions stably by coupling with auxiliary subunits (BKIP [6], ISLO-1 [7]), a cytoskeletal protein (a-catulin [8,9]) and the dystrophin complex [11] and its components (DYS-1 [10], dystrobrevin [5]). In addition to forming the dystrophin complex, cav3 also functions as signal domains [30] and interacts with voltage-dependent Ca 2+ channel [31] and ryanodine receptor 1 (RyR1) [23,32], and contributes to excitation-contraction coupling (E-C coupling) [33].…”
Section: Caveolin-3 Interacted With Bk Ca Channel Via Caveolin-1 Bindmentioning
confidence: 99%
“…In the previous study, we have shown the direct and functional interaction of BK Ca channel with cav1 to form functional molecular complex in living vascular smooth muscle cells and also in HEK293 expression system [19]. It remains, however, to be determined whether BK Ca channel directly interacts with cav3, whereas the possible functional interaction between BK Ca channel and dystrophin complex including cav3 in skeletal muscle has been suggested [5,11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation